DIRECT INVESTMENT STRATEGY IN DOMESTIC HAJJ FINANCIAL GOVERNANCE - Muh Arafah Ali; Siska Mandalia (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
This paper aims to find strategies that can be carried out by BPKH in domestic hajj financethrough direct investment. This paper includes a literature study with a normative approach by takingdata sources from the laws and regulations on haj fund management and the book “What and How toInvest in BPKH Hajj Finance. As well as from books, journals and from the internet in the form of newsrelated to investment finance hajj. Data analysis techniques and data presentation used in this study werequalitative descriptive analysis. The results obtained show that the first direct investment strategy indomestic hajj financial governance, has its own business, second, capital participation, third, investmentcollaboration, fourth, other direct investment. Examples of businesses that can be run in investment,transportation, lodging or hotels, business convection and providing gifts or gifts.